2010
DOI: 10.1093/schbul/sbq060
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal and Striatal Volumes in Monozygotic Twins Concordant and Discordant for Schizophrenia

Abstract: Frontostriatal networks mediating important cognitive and motor functions have been shown to be abnormal structurally and functionally in schizophrenia. However, the influence of genetic risk for schizophrenia on structural abnormalities in these areas is not well established. This study therefore aimed to investigate prefrontal and striatal volume alterations in schizophrenia and to define the extent to which they are dependent on genetic vulnerability for the condition. We employed structural magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 77 publications
2
22
0
1
Order By: Relevance
“…No differences [48] ARMS > HC: Recognition during false alarms vs correct recognition: hippocampus + Response initiation and suppression: R caudate and bil ACC [48] ( Our results are in line with recently published meta-analyses and studies, which found reduced GMV in the anterior cingulate [18,72], prefrontal [8,73], the temporal cortex [73,74] and in the thalamic region [72] in the subjects prone to psychosis compared to HC. The tendency to develop psychosis, seen especially in G-HR compared to the HC group (genetic diathesis [73]), related to slightly different brain regions as compared to the changes associated with prodromal symptoms (C-HR vs. HC group).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No differences [48] ARMS > HC: Recognition during false alarms vs correct recognition: hippocampus + Response initiation and suppression: R caudate and bil ACC [48] ( Our results are in line with recently published meta-analyses and studies, which found reduced GMV in the anterior cingulate [18,72], prefrontal [8,73], the temporal cortex [73,74] and in the thalamic region [72] in the subjects prone to psychosis compared to HC. The tendency to develop psychosis, seen especially in G-HR compared to the HC group (genetic diathesis [73]), related to slightly different brain regions as compared to the changes associated with prodromal symptoms (C-HR vs. HC group).…”
Section: Discussionsupporting
confidence: 91%
“…Several centers worldwide are fo-*Address correspondence to this author at the Department of Psychiatry, University of Basel, c/o University Hospital Basel, Petersgraben 4, Basel 4031, Switzerland; Tel: +41 61 265 50 40; Fax: +41 61 265 45 88; E-mail: renata.smieskova@upkbs.ch cusing on high-risk state for psychosis individuals with the aim to investigate the process. High-risk individuals can be identified according to their putative endophenotypes as genetic high-risk individuals (G-HR; [7][8][9]) or according to their clinical symptoms as clinical (ultra) high-risk (C-HR, UHR) or 'at-risk mental state' (ARMS, [10][11][12]) individuals. G-HR samples include monozygotic and dizygotic twins discordant for schizophrenia (non-psychotic twin) and/or subjects with at least two first-or second-degree relatives of patients affected with psychosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this model, genetic and/or environmental insults are thought to occur prenatally, during early childhood or adolescence, and lead to the later emergence of psychotic symptoms (Lewis and Levitt 2002; Rapoport et al 2012; Owen et al 2011; Weinberger and Lipska 1995; Bayer et al 1999). This model is supported by findings of reduced cortical volumes and increased ventricle size at the onset of schizophrenia (Cannon et al 2002; Ettinger et al 2012; Jones et al 1994). Alternatively, the late neurodevelopmental model advocates for schizophrenia risk factors derived from a faulty synaptic pruning during adolescence (Feinberg 1982) and is supported by progressive reductions of gray matter volume during the earliest stages of psychosis in subjects that convert to schizophrenia (Pantelis et al 2005; Sun et al 2009; Borgwardt et al 2008).…”
Section: Introductionmentioning
confidence: 52%
“…Previous region of interest studies of discordant MZ twin pairs have detected unique environmentally determined volume deficits in frontal, 13 hippocampal 9,42 and lateral ventricular volumes 10 and in the insula, superior temporal gyrus, posterior cingulate, left superior and medial frontal gyrus and right anterior cingulate gyri. 15 Cortical surface mapping has revealed environmentally driven differences in grey matter density in the dorsolateral prefrontal cortex, superior temporal gyrus and superior parietal lobule.…”
Section: Unique Environmental Effectsmentioning
confidence: 87%
“…Twin studies are a method to circumnavigate this challenge, though the findings of twin studies in schizophrenia have been inconsistent. The majority adopted region of interest methods and reported that monozygotic (MZ) discordant twins with schizophrenia have larger lateral ventricles; 8 smaller grey matter, hippocampal and hypothalamic volumes; [9][10][11][12] and smaller thalamic and frontal volumes 13,14 than their nonpsychotic co-twins, implicating unique environmental effects.…”
Section: Introductionmentioning
confidence: 99%